Large-scale fabrication of translucent, stretchable and durable superhydrophobic composite films. Issue 45 (1st November 2017) - Wang, Shanlin; Yu, Xinquan; Zhang, Youfa
Abstract : Transplantable superhydrophobic films with comprehensive performance in translucence, thermal tolerance, stretchability, impact resistance, wear resistance, anti-corrosion, and self-cleaning. Abstract : Nano-scale textures with special wettability impart a broad spectrum of unique properties to the superhydrophobic surfaces that can be applied in various fields. However, there are still many difficulties in large-scale practical applications due to the limitation of the service life of superhydrophobic materials. In this study, we developed a type of novel transplantable superhydrophobic film by two-step spray methods and subsequent demoulding. The comprehensive performances of the film were investigated in translucence, thermal tolerance, stretchability, impact resistance, wear resistance, anti-corrosion, and self-cleaning. The results show that the surface can maintain its superhydrophobicity and color after treatment at 150 °C for 24 h. Further testing revealed that the superhydrophobicity of the film was not lost after toleration of strain up to 100%, impacting by water or weight, man-made destruction by hands or sandpaper, immersing in various corrosive liquids, and pollution by sludge water or dirt. These multiple key properties that have been integrated into our superhydrophobic composite film are expected to provide unique advantages for a wide range of applications in decoration, construction, transport, electronics, and wearable devices.